Estructuras + en funtores fibrados de biconjuntos e ideales en funtores de Green en biconjuntos - Calderón León, José Miguel (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
Before delving into the work accomplished, it is important to note that it focuses on two fundamental problems. The first involves the generalization of the method employed by Bouc [7], where the Burnside functor with coefficients in Q, denoted as QB, was explored. This Green functor of biconsets exhibits the property of being a commutative Q-algebra of semisimple finite dimension that splits in each evaluation. A detailed characterization of its ideals has been provided. The second addressed problem entails the generalization of the structures presented by Boltje, Raggi, and Valero in [4]. These structures, originally designed for functors of biconsets, are now extended to functors of fibrated biconsets. The essential condition is that the resulting structures match those provided in [4] when the fiber is the trivial group {·}.

En este trabajo está divido en 2 problemas. El primero de ellos es generalizar el método utilizado por Bouc en [7], donde estudió el funtor de Burnside con coeficientes en Q, denotado por QB, el cual es un funtor de Green de biconjuntos tal que en cada una de sus evaluaciones es una Q-álgebra conmutativa de dimensión finita semisimple que se escinde, al cual se le dio una caracterización de sus ideales. El segundo de los problemas es dar una generalización de las estructuras dadas en [4] por Boltje, Raggi y Valero para funtores de biconjuntos fibrados en lugar de funtores de biconjuntos, las estructuras que se darán deben de coincidir con las estructuras dadas en [4] cuando la fibra es el grupo trivial {·}
Instituto de Física y Matemáticas. Facultad de Ciencias Físico Matemáticas. Unidad Morelia del Instituto de Matemáticas de la UNAM. Posgrado Conjunto de Doctorado en Ciencias Matemáticas
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16591; info:eu-repo/classification/cti/1; IFM-D-2023-1467; Funtores de biconjuntos; Funtores de Green; Ideales